EVALUASI KEBUTUHAN RUANG PARKIR SEPEDA MOTOR DI AREA GEDUNG FKIP DAN FST UNIVERSITAS QOMARUL HUDA BADARUDDIN BAGU: Evaluation of Motorcycle Parking Space Needs in the FKIP and FST Building Area of Qomarul Huda University Badaruddin Bagu - Januriad Januriad; Bagus Widhi Dharma S.; Yuliarti Utami (Yayasan Al-Amin Qalbu, 2023)
Parking is a problem that is often encountered in terms of transportation, especially in locations that have high activity, one of which is on campus. This study discusses the need for parking space in the FKIP UNIQHBA and FST Building Areas. The research method used for the preparation of this study was a quantitative method by anticipating work and then conducting field surveys at the parking locations of the FKIP and FST UNIQHBA Buildings based on the Directorate General of Land Transportation in 1998). The results of the research on parking characteristics obtained include: the maximum parking duration of a motorcycle is 525 minutes, the average duration of a motorcycle is 222.76 minutes. The accumulation of motorcycle parking is 221 vehicles. The maximum parking volume for motorbikes is 414 vehicles during the survey (07.00-17.00). motorcycle parking index of 202.75%. Motorcycle parking turnover is 2.04 times. The static capacity in the FKIP and FST UNIQHBA Building Area is 109 SRP. Maximum motorcycle occupancy is 202.75% (10.30-10.45 hours). Parking Space Requirement (KRP) that must be provided for motorcycle parking is 243 SRP. From the results of the overall calculation analysis, it can be concluded that the existing parking space capacity is not sufficient, there is still a shortage of 134 SRP for motorcycles